Utilization of ICT by Students with Visual Impairment - Qureshi, Maria Sohaib; Humara Bano (JIE, 2023)
Children with disabilities are given equal rights for information accessibility as mentioned in the “Convention on the Rights of Person with Disability”. The study aimed to explore the actual role of information communication technologies in imparting information to students with visual impairments. For this, the data was collected from 41male and female students with visual impairment using android mobiles, computer/laptops, or using internet facilities at libraries of their academic institutions. It involves quantitative data gathering techniques following snowball sampling procedure. Findings indicates that:(a) mobile has been identified as thebest source to access information to enhance literacy among students (females) with visual impairment followed by Laptop/Desktop Computer and web browsing respectively (b) girls are using information communication technologies more effectively for their digital literacy as compared to male students with visual impairment and c) girls are facing more constraints in accessing information as compared to male students with visual impairment. The effort made by this study is helpful to develop awareness among the stakeholders of the field and particularly to sensitize the heads of teaching institutions and government to enhance the provision of more computer labs with internet browsing services to enhancedigital literacy among students with visual impairment.